IMPLEMENTATION OF IMMIGRATION FUNCTIONS AS IMMIGRATION LAW ENFORCEMENT IN THE FRAMEWORK OF NONPROCEDURAL MIGRANT INDONESIAN WORKERS - Rahma Iria Mayang Anggreini; Anita Herlina (Journal of Law and Border Protection, 2019)
Indonesia is one of the largest contributors to migrant workers in ASEAN. The large number of Indonesians who have links to become Indonesian Migrant Workers or PMI have started to cause unrest with the criteria for non-procedural Indonesian migrant worker who work without using valid or incomplete documents. The existence of non-procedural migrant worker poses a greater risk of crimes that can occur to migrant workers, considering that they are non-procedural migrant workers who are not bound and protected by the law that works on Indonesian Migration Workers, namely Law Number. 18 of 2017. Membership is not the broad coverage of this legal basis, coupled with the low level of public understanding of the law, and the consequences of its mistakes and weak law enforcement are the main causes of the circulation of non-procedural migrant workers which eventually become victims of crimes that may occur such as exploitation, abuse, national, persecution, smuggling, and human trafficking to become victims of murder. Immigration as a government agency associated with indonesian migrant worker carries out its function partly as public and legal service. Law enforcement carried out by immigration officials, namely monitoring to providing criminal acts, is a form of law enforcement carried out by immigration to provide protection to PMI and prevent non-procedural PMI sending.